Nuclear quadrupole moments as a microscopic probe to atudy the motion of atomic tunneling systems in amorphous solids - Bartkowiak, Marek; Bazrafshan, Masoomeh; Fischer, Christian; Fleischmann, Andreas; Enss, Christian (Physical review letters, 2013)
The properties of amorphous solids below 1 K are dominated by atomic tunneling systems. A basic description is given by the standard tunneling model. Despite its success, the standard tunneling model still remains phenomenological and little is known about the microscopic nature of tunneling systems in amorphous solids. We present dielectric polarization echo experiments on partially deuterated amorphous glycerol. Nuclear quadrupoles, introduced by the deuteration, influence the echo amplitude in a characteristic way and allow us to draw for the first time detailed conclusions about the microscopic nature of the tunneling processes in amorphous glycerol.